De la justicia local a la justicia global: a propósito de las sociedades “atípicas” - Muñoz Sandoval, Daniela (2023)
In Colombia, atypical corporations are formed when, in the process of incorporation, none of the organizational forms provided by law are adopted, which is considered an instance of defective incorporation that gives rise to de facto corporations. However we could speak about atypical corporations from another perspective — that of the globalized le gal market. The demands of globalization also affect the business world, which makes it necessary to address this reality and evaluate, first, the possibility of establishing commercial companies that conform to the interests of its members, and, second, t o determine possible solutions to the problems that may arise when introducing such an innovative figure.